A PROPOSED THEORETICAL FRAMEWORK ON IMPROVING COMPLIANCE BEHAVIOUR TOWARDS LEGAL METROLOGY VERIFICATION: THE CASE OF METROLOGY CORPORATION MALAYSIA SDN. BHD. (MCM) - Muhammad Iqbal Balative (Journal of Islamic Management Studies, 2021)
As we all know, moral precepts to ensure the integrity of the measurements were contained within the holy books - e.g. the Qur’an, Torah, and Bible and in The Analects (Lun Yu) of Confucius and in the early India Arthashastra of Kautilya. Compliance of the business owners to verify their weights and measures instruments are important and depending on several factors. Qualitative research methodology was used where a thorough review of literature on compliance behavior in the metrology verification in general and the available literature on Metrology Corporation Malaysia Sdn. Bhd (MCM) as well as interviews were conducted, the results suggested the norms, attitude, perceived behavioral control and knowledge to be positively and significantly correlated with compliance behavior of business owners towards legal metrology verification.